The De morte testamentoque Alexandri Magni Liber. Spanish Translation, with an Introduction and notes (Circe de clásicos y modernos, 2025)
This paper provides the first translation from Latin into Spanish of the anonymous text traditionally known as De morte testamentoque Alexandri Magni liber, written in the late 4th or early 5th century AD. The translation is accompanied by an introduction that briefly summarizes the textual transmission and overall interpretations of this work. Brief notes with textual, historical, and cultural commentary are also included.
Keywords: Alexander the Great; Late Antiquity; Metz Epitome; Alexander Romance; Liber de morte